Adaptive Management Process Of Miri District To Face Covid-19 Of 2020 - Veni Tusiana; Rita Noviani; Yasin Yusup (Universitas Sebelas Maret, 2020)
COVID-19 has an impact in Indonesia, both directly, namely related to public health, and indirectly, namely other impacts caused in various fields in an area. This has an impact on Miri District, Sragen Regency, Central Java. Although there has been no confirmation of a positive case of COVID-19 in Miri District, it is important to conduct research related to the adaptation management process of the Miri Subdistrict community in dealing with COVID-19. The method used in this research is descriptive qualitative with the interactive model analysis technique of Miles and Huberma. The results of the analysis show that the adaptation management process of the Miri Subdistrict community in dealing with COVID-19 is marked by a series of moments of the spread of COVID-19 which can be divided into three stages. The form of adaptation at each stage shows different conditions. The initial stage is marked by the stability of social and economic conditions, the stage of policy implementation is marked by disruption of social and economic conditions, and the stage towards a New Normal is marked by the return to stability of the economic conditions of the people of Kemiri District.